Understanding investigators' attitudes through a results-based accountability framework within a single CTSA institution. Issue 1 (13th January 2017) - Rothwell, Erin; Matheson, Trent
Abstract : Purpose: The National Center for Advancing Translation Science (NCATS) is implementing a new strategic management plan called the results-based accountability framework. This framework is part of the common metrics initiative. For successful implementation and adoption of new management strategies, it is important to assess current stakeholders' experiences and needs. Methods: Interviews were conducted with principal investigators who are conducting research and supported by the Center for Clinical Translational Science at the University of Utah. Between July and August 2016, 15 interviews were completed and audio recorded. A qualitative content analysis was conducted on the transcripts. Results: Results indicated the need to provide education about the continuum of clinical translational research; time constraints during pre-award; barriers to IRB submissions; difficulty balancing other responsibilities in academic health centers; and the need for shared study coordinator resources. Conclusion: Implementing a new management philosophy requires an understanding key stakeholders attitudes and needs. The research identified ways to help engage investigators with centralized resources supported by NCATS and implementation of common metrics at this university.